2024
DOI: 10.1103/prxquantum.5.020303
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Control of Radical-Pair Dynamics beyond Time-Local Optimization

Farhan T. Chowdhury,
Matt C.J. Denton,
Daniel C. Bonser
et al.

Abstract: We realize arbitrary-wave-form-based control of spin-selective recombination reactions of radical pairs in the low-magnetic-field regime. To this end, we extend the gradient-ascent pulse engineering (GRAPE) paradigm to allow for optimizing reaction yields. This overcomes drawbacks of previously suggested time-local optimization approaches for the reaction control of radical pairs, which were limited to high biasing fields. We demonstrate how efficient time-global optimization of the recombination yields can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Here we have demonstrated that the QFI, and the quantum Cramér-Rao bound it sets on precision, is an effective tool, in addition to the conventional contrast measure, to assess fundamental limits of precision of different radical models against one another in the limits of biological complexity and identify opportunities to improve upon nature's design principles [107,108]. Furthermore, it provides scope for future studies to analyse additional mechanisms, such as driven radical motion, and elucidate those that provide the optimal enhancements in precision, thereby giving insight into how nature may achieve exquisite magnetic field sensitivity and how we can optimise it for technological applications.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have demonstrated that the QFI, and the quantum Cramér-Rao bound it sets on precision, is an effective tool, in addition to the conventional contrast measure, to assess fundamental limits of precision of different radical models against one another in the limits of biological complexity and identify opportunities to improve upon nature's design principles [107,108]. Furthermore, it provides scope for future studies to analyse additional mechanisms, such as driven radical motion, and elucidate those that provide the optimal enhancements in precision, thereby giving insight into how nature may achieve exquisite magnetic field sensitivity and how we can optimise it for technological applications.…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of quantum biology is to apply theory-driven predictions for multi-scale integration of cellular function. It is of paramount importance to identify magnetic field parameters to modulate quantum coherences in a radical pair reaction [8,9,31,32]. Here, we make the quantum coherence and singlet product yield indistinguishable.…”
Section: Introductionmentioning
confidence: 99%